TEKNIK BIOREMEDIASI SEBAGAI SOLUSI DALAM UPAYA PENGENDALIAN PENCEMARAN LINGKUNGAN : LITERATUR REVIEW - Endah Rita Sulistya Dewi; Atip Nurwahyunani, Erma Lintang Sari, Farisa Khoirun Nissa, Merlly Alfina Septiana, Diska R.P. Andri (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Pollution is the entry or introduction of living organisms, energy substances, and/or other components into the environment. The increasing pollution of air and water, as well as the contamination of the soil, contributes to environmental degradation. Inadequate waste management that leads to environmental damage prompts the exploration of solutions, and one option is to employ bioremediation techniques for polluted air, water, and contaminated soil. This research involves a literature review of articles on bioremediation, aiming to outline bioremediation techniques as an alternative solution to environmental pollution. The investigation process includes 16 articles, which are then analyzed. The literature review results indicate that bioremediation techniques, such as phytoremediation, bioaugmentation, and biostimulation, are widely employed as environmental solutions. The findings from the literature review are expected to contribute recommendations for the application of bioremediation in addressing environmental pollution caused by waste